Psychosocial Impact of COVID-19 on Healthcare Workers - Yazdanfar, Maryam; Bachuwa, Ghassan; Rios-Bedoya, Carlos; Khaneki, Sina (International Journal of Psychosocial Rehabilitation, 2024)
COVID-19 pandemic has significantly impacted frontline workers over the past year. It isessential to evaluate the psychosocial impact of this pandemic on Healthcare workers tominimize the negative impacts of this pandemic as well as potential pandemics in the future inthis group. Many of these individuals have been experiencing high levels of stress and symptomsof both anxiety and depression. This is exceptionally worrisome as if left untreated, can lead tolong-term mental health problems.Since December 2019, many people have been infected with the coronavirus around the world.Today, there are more than140millionconfirmed cases of coronavirus globally, with more thanthree million deaths as a result of this disease (COVID-19 situation update worldwide, 2020). Inmany ways, this virus has caused fear, stress, anxiety, and adverse psychosocial impacts. TheNational Health Commission of China has released multiple reports about the mental healthcrisis related to coronavirus and its negative emotional, psychological, and social impacts on themedical workers (Kang et al., 2020). According to a recent article by Lai et al., there is a great  concern on social and mental pressures on healthcare professionals during an outbreak. Otherrecent study suggested that compare to the general population, healthcare workers were morelikely to experience the burden of depression, mainly because of fear of getting infected andpassing it on to their family members and loved ones, lack of personal protective equipment, andworking too many hours during the COVID19 pandemic (Krishnamoorthy et al., 2020).Previousreports have shown that in similar events in the past such as sever acute respiratorysyndrome(SARS) and Middle East respiratory syndrome (MERS) outbreaks, healthcareprofessionals experienced a great level of anxiety, fear, mental pressure, and symptoms ofdepression even after control of the outbreak. Moreover, recent data have shown the mostunderestimated problem during this pandemic is every day increase of workload on healthcareprofessionals which can be triggered to developing anxiety and psychiatric disorders (DelgadoGallegos et al., 2020). In a study by Wang et al., during the initial phase of an outbreak acrossChina, more than half of participants reported as experiencing a moderate to severepsychological impact and with over a third of them showed signs of moderate to severe anxiety.At this time, the main focus of public health departments and the World Health Organization ison how to prevent the spread of COVID-19 and protect our healthcare workers from exposure.Therefore, further research is necessary to study the pandemic's holistic impacts and look intoways to promote mental wellbeing among healthcare workers. The objective of our study is toevaluate the impact of COVID-19 on healthcare workers at Hurley Medical Center and identifyindividuals at highest risk to establish preventative interventions to ameliorate the negativeimpact of similar events on the vulnerable population in the future.